2002
DOI: 10.1067/mtc.2002.127313
|View full text |Cite
|
Sign up to set email alerts
|

Operative classification of thromboembolic disease determines outcome after pulmonary endarterectomy

Abstract: The degree of improvement in pulmonary hypertension and tricuspid regurgitation after pulmonary endarterectomy is determined by the type and location of pulmonary thromboembolic disease. Classification of thromboembolism is useful for predicting patient outcome after pulmonary endarterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
186
1
18

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(209 citation statements)
references
References 24 publications
4
186
1
18
Order By: Relevance
“…In their study, Thistlethwaite and colleagues divided patients into 4 groups, according to intraoperative classification 30 : type 1, fresh thrombus in the main-lobar pulmonary arteries; type 2, intimal thickening and fibrosis proximal to segmental arteries; type 3, disease within distal segmental arteries only; type 4, distal arteriolar vasculopathy. In the present series, all patients with central type (CD score ≥2) had type 1 or 2, whereas of the patients with relatively peripheral type, 2 patients with a CD score of 0 were type 3, and 1 patient with a CD score of 1 was type 4.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Thistlethwaite and colleagues divided patients into 4 groups, according to intraoperative classification 30 : type 1, fresh thrombus in the main-lobar pulmonary arteries; type 2, intimal thickening and fibrosis proximal to segmental arteries; type 3, disease within distal segmental arteries only; type 4, distal arteriolar vasculopathy. In the present series, all patients with central type (CD score ≥2) had type 1 or 2, whereas of the patients with relatively peripheral type, 2 patients with a CD score of 0 were type 3, and 1 patient with a CD score of 1 was type 4.…”
Section: Discussionmentioning
confidence: 99%
“…Both had significant distal disease on pre-operative assessment. The remainder of the operable group were surgically classified at the time of operation (using the THISTLETHWAITE et al [9] classification) as predominantly type II/III disease and adjudged to have good technical clearance (table 1).…”
Section: Subjectsmentioning
confidence: 99%
“…[4][5][6] In addition, a previous study showed that patients with a PVR greater than 1,100 dynes·sec −1 ·cm −5 and an mPAP greater than 50 mmHg had a poor outcome. 8) Jamieson et al also reported that 17 of 22 hospital deaths (77%) were related to residual pulmonary hypertension, and the mortality rate was 31% when the postoperative PVR was >500 dynes·sec ·cm −5 in case 2.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, for patients with distal pulmonary artery disease, PEA is, technically, more difficult and, obviously, its outcome is much poorer than that of proximal disease. [4][5][6][7] In our previous study, we also reported that the mortality of proximal and distal disease after PEA was 3.9% and 13.5%, respectively. 7) In this report, we present two exceptionally difficult cases of severe CTEPH with proximal lesions who died from residual pulmonary hypertension after effective likelihood PEA.…”
mentioning
confidence: 99%